La cebra Camila - Nunez, Marisa; Villan, Oscar (Pontevedra : Kalandraka, 2000)
Camila does not listen to her mother and goes outside without her suspenders and pants. A strong wind comes and blows her stripes in all directions. The other animals come to her aid.
Original title in Portuguese : "A cebra Camila".
Accelerated Reader AR
Keywords: Zebras -- Juvenile fiction; Spanish language materials -- Juvenile fiction; Cebras -- Novela juvenil; Picture books